Modulated illumination localization microscopy-enabled sub-10 nm resolution - Yile Sun; Lu Yin; Mingxuan Cai; Hanmeng Wu; Xiang Hao; Cuifang Kuang; Xu Liu (Journal of Innovative Optical Health Sciences, 2022)
Optical microscopy is an essential tool for exploring the structures and activities of cells and tissues. To break the limit of resolution caused by diffraction, researchers have made continuous advances and innovations to improve the resolution of optical microscopy since the 1990s. These contributions, however, still make sub-10[Formula: see text]nm imaging an obstacle. Here, we name a series of technologies as modulated illumination localization microscopy (MILM), which makes ultra-high-resolution imaging practical. Besides, we review the recent progress since 2017 when MINFLUX was proposed and became the inspiration and foundation for the follow-up development of MILM. This review divides MILM into two types: point-scanning and wide-field. The schematics, principles and future research directions of MILM are discussed elaborately.